2017
DOI: 10.2352/issn.2470-1173.2017.8.maap-281
|View full text |Cite
|
Sign up to set email alerts
|

Model-based Skin Pigment Cartography by High-Resolution Hyperspectral Imaging

Abstract: The determination of local components in human skin from in-vivo spectral reflectance measurements is crucial for medical applications, especially for aiding the diagnostic of skin diseases. Hyper-spectral imaging is a convenient technique since one spectrum is acquired in each pixel of the image, and by inverting a light scattering model, we can retrieve the concentrations of skin components in each pixel. The good performance of the method presented in this paper comes from both the imaging system and the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 18 publications
0
18
0
Order By: Relevance
“…This technology allows the user to select specific wavelength to assess the presence of melanin and haemoglobin, as well as performing nCDA of the overall dark circle area. 17 Some published articles have already highlighted the benefit of this technique to assess skin colour, 18 and even more specifically, skin pigment, 19 erythema, 20 melanin, total haemoglobin and oxygen saturation in dark circles. 21 The multispectral analysis performed in this research showed a higher melanin index that suggests hyperpigmentation, and a higher haemoglobin index that supports the hypothesis of blood vessel dilation in the dark circles area.…”
Section: Discussionmentioning
confidence: 99%
“…This technology allows the user to select specific wavelength to assess the presence of melanin and haemoglobin, as well as performing nCDA of the overall dark circle area. 17 Some published articles have already highlighted the benefit of this technique to assess skin colour, 18 and even more specifically, skin pigment, 19 erythema, 20 melanin, total haemoglobin and oxygen saturation in dark circles. 21 The multispectral analysis performed in this research showed a higher melanin index that suggests hyperpigmentation, and a higher haemoglobin index that supports the hypothesis of blood vessel dilation in the dark circles area.…”
Section: Discussionmentioning
confidence: 99%
“…SpectraCam ® (Newtone Technologies, Lyon, France) is a portable camera that collects in vivo reflectance data from human skin ( Figure 1 21 Light emitted by LEDs is transmitted through the polarizers (P) and reflected by the skin. A tunable filter (TF) let pass a specific wavelength and is used as analyzer.…”
Section: The Spectracam ® Hyperspectral Imaging Systemmentioning
confidence: 99%
“…However, as the computation time needed to analyze the spectral information increases proportionally to the number of pixels, the skin model and the optical model chosen should be as simple as possible, to make the time needed for data analysis acceptable. In a previous work [5], a Kubelka-Munk inspired model applied onto a two-layer skin structure was shown to give satisfactory results by computing up to five skin composition maps of 1120 × 900 pixels in less than one hour. The hyperspectral images were captured by using the SpectraCam® camera [5] [10] developed by Newtone Technologies.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, research in the measurement of skin optical properties has focused on non-invasive in vivo methods as ex vivo methods are known to alter the properties of the skin, and as invasive analysis may cause patient discomfort. Several optical methods have emerged, such as diffuse reflectance spectroscopy [2], modulated imaging [3], spectral imaging, and color imaging [4] [5]. Data retrieved from these methods have been analyzed using various models such as the Monte Carlo method [6], the radiative transfer equation [7], the diffusion approximation [3], flux models such as the Kubelka Munk model [5], and independent component analysis [8].…”
Section: Introductionmentioning
confidence: 99%